A biodegradable synthetic resin and preparation method thereof

By adopting a synthetic resin with a three-layer coextruded film structure, cellulose aerogel and pentaerythritol epoxy oleate combined as a compatibility agent, the thermodynamic incompatibility of PLA and PBAT is solved, the interface compatibility and mechanical properties are improved, the cost is reduced, and good degradation performance is maintained during the biodegradation process.

CN119432034BActive Publication Date: 2025-03-28SHENZHEN HONGCAI NEW MATERIAL TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510037559.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-28
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

As a thermodynamic incompatible system, PLA and PBAT have large interface tension, weak interface adhesion, poor mechanical properties, and the existing compatibilizers are complex in structure, difficult to prepare, high cost, and will increase the difficulty in the early stages of biodegradation.

Method used

The synthetic resin with a three-layer coextruded film structure is used, and the thickness ratio of the outer layer, middle layer and inner layer is 1:2:1. The interfacial compatibility between PLA and PBAT is improved by combining cellulose aerogel and pentaerythritol epoxy oleate as a compatibility agent.

Benefits of technology

It improves the interface compatibility between PLA and PBAT, has good product uniformity, excellent mechanical properties, low cost, and will not increase the initial difficulty during the biodegradation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432034B_ABST
    Figure CN119432034B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of synthetic resins, specifically a biodegradable synthetic resin and a preparation method thereof, wherein the synthetic resin is a three-layer co-extruded film consisting of an outer layer, a middle layer and an inner layer; the outer layer includes the following components: racemic polylactic acid, ethyl cellulose, silane coupling agent KH-560 and carnauba wax; the middle layer includes the following components: PLA, PBAT, cellulose aerogel, epoxy oleic acid pentaerythritol ester, liquid paraffin and stearic acid; the inner layer includes the following components: polyhydroxyalkanoate, left-handed polylactic acid, ethylene-acrylate-maleic anhydride copolymer, acetylcitrate tributyl, TMP and tert-butylhydroquinone. The present invention uses PLA and PBAT as the main materials of the middle layer, and uses cellulose aerogel and epoxy oleic acid pentaerythritol ester as a compatibilizer after being compounded to improve the interface compatibility of PLA and PBAT, and the product has good uniformity and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of synthetic resins, in particular to a biodegradable synthetic resin and a preparation method thereof. Background Art

[0002] Polylactic acid (PLA) and butylene terephthalate adipate (PBAT) are both biodegradable materials. PLA has natural antibacterial properties, but its toughness is poor; while PBAT does not have natural antibacterial properties, it has excellent toughness and impact strength. Therefore, PLA and PBAT are complementary in performance, but PLA and PBAT are thermodynamically incompatible systems, with large interfacial tension between the two phases, weak interfacial adhesion, and poor mechanical properties.

[0003] The Chinese invention patent with publication number CN111378259B discloses a biodegradable PBAT / PLA composite material and its preparation method and use. The method uses a compound with a special structure as a compatibilizer. The structure of the compatibilizer contains highly active reactive groups such as epoxy groups, double bond groups, and hydroxyl groups. It is difficult to prepare and the price is relatively high. The highly active reactive groups in the compatibilizer react with the free radicals or terminal groups in PLA and PBAT to form new polymer chains, which will increase the difficulty of the biodegradation process of PLA and PBAT in the early stage of biodegradation. In addition, the functional groups of the compatibilizer can react with the groups generated during the degradation of the polymer, and compete with PLA and PBAT for biodegradation, which will also increase the difficulty of initial biodegradation. Summary of the invention

[0004] The object of the present invention is to provide a biodegradable synthetic resin and a preparation method thereof to solve the problems raised in the above background technology.

[0005] To achieve the above object, on the one hand, the present invention provides the following technical solutions: a biodegradable synthetic resin, the synthetic resin is a three-layer co-extruded film consisting of an outer layer, a middle layer and an inner layer, the thickness ratio of the outer layer, the middle layer and the inner layer is 1:2:1;

[0006] The outer layer comprises the following components by weight: 50 to 75 parts of racemic polylactic acid, 30 to 55 parts of ethyl cellulose, 8 to 10 parts of silane coupling agent KH-560 and 6 to 8 parts of carnauba wax;

[0007] The middle layer comprises the following components by weight: 40-45 parts of PLA, 20-32 parts of PBAT, 12-16 parts of cellulose aerogel, 8-10 parts of pentaerythritol epoxy oleate, 0.5-1 parts of liquid paraffin and 0.5-1 parts of stearic acid;

[0008] The inner layer comprises the following components by mass: 65-80 parts of polyhydroxyalkanoate, 18-24 parts of L-polylactic acid, 12-15 parts of ethylene-acrylate-maleic anhydride copolymer, 2-4 parts of acetyl tributyl citrate, 1-2 parts of TMP6000 and 0.1-0.5 parts of tert-butyl hydroquinone;

[0009] The preparation method of the synthetic resin comprises the following steps:

[0010] S1. Mixing the outer layer components: firstly put the racemic polylactic acid, ethyl cellulose and carnauba wax into a vacuum oven, vacuum dry them at 45-50°C for 8-10h, then transfer them into an internal mixer, add silane coupling agent KH-560 into the internal mixer, set the blending temperature at 180-200°C, the blending speed at 50-70r / min, and finally melt-blend for 5-10min to obtain blend A;

[0011] S2, mixing the middle layer components: first put PLA and PBAT into a vacuum oven, vacuum dry them at 45-50°C for 8-10 hours, and then transfer them to an internal mixer, then put the cellulose aerogel into a container and place it in a vacuum chamber, evacuate to 98.7-99.9 kPa at room temperature, then gradually add pentaerythritol epoxy oleate, ultrasonically stir for 2-5 hours, and then transfer to an internal mixer, then add liquid paraffin, acetyl tributyl citrate and stearic acid to the internal mixer, set the blending temperature to 180-200°C, the blending speed to 50-70 r / min, and finally melt blend for 5-10 minutes to obtain blend B;

[0012] S3, mixing the inner layer components: first put the polyhydroxyalkanoate and L-polylactic acid into a vacuum oven, vacuum dry them at 45-50°C for 8-10 hours, and then transfer them to an internal mixer, then add ethylene-acrylate-maleic anhydride copolymer, acetyl tributyl citrate, TMP6000 and tert-butylhydroquinone into the internal mixer, set the blending temperature to 180-200°C, the blending speed to 50-70r / min, and finally melt-blend for 5-10 minutes to obtain a blend C;

[0013] S4, three-layer co-extrusion: firstly, the blend A, the blend B and the blend C are respectively put into the outer material flow channel, the middle material flow channel and the inner material flow channel of the three-layer co-extrusion film blowing machine, and then the blend A, the blend B and the blend C are respectively heated to be melted and extruded from the die head of the three-layer co-extrusion film blowing machine to obtain a mold blank, and finally the mold blank is blown into a film bubble by a blow molding machine;

[0014] S5, cooling and winding: firstly cool the film bubble to room temperature, then use a film edge trimming machine to trim the film bubble, and finally use a film winding machine to wind up the film bubble to obtain the synthetic resin.

[0015] Optionally, the density of the racemic polylactic acid is 1.26 g / cm3 The melt index of the racemic polylactic acid is 6.5 g / 10 min.

[0016] Optionally, the density of the PLA is 1.24 g / cm 3 The melt index of PLA is 6.1 g / 10 min, and the density of PBAT is 1.20 g / cm 3 , the melt index of the PBAT is 42.8 g / 10 min.

[0017] Optionally, the PLA is a mixture of racemic polylactic acid and L-polylactic acid, and the mass ratio of racemic polylactic acid to L-polylactic acid is 1:1.

[0018] Optionally, the density of the polyhydroxyalkanoate is 1.28 g / cm 3 The melt index of the polyhydroxyalkanoate is 4.0 g / 10 min, and the density of the L-polylactic acid is 1.25 g / cm 3 The melt index of the L-polylactic acid is 7.0 g / 10 min.

[0019] Optionally, the outer material flow channel is connected to a first screw extruder, and the temperature parameters of the first screw extruder are set as follows: zone 1 is 154-174°C, zone 2 is 165-185°C, zone 3 is 166-186°C, zone 4 is 166-186°C, and zone 5 is 165-185°C;

[0020] The middle-layer material flow channel is connected to the second screw extruder, and the temperature parameters of the second screw extruder are set as follows: zone 1 is 166-186°C, zone 2 is 117-197°C, zone 3 is 178-198°C, zone 4 is 179-199°C, and zone 5 is 178-197°C;

[0021] The inner material flow channel is connected to the third screw extruder, and the temperature parameters of the third screw extruder are set as follows: zone one is 169-185°C, zone two is 180-200°C, zone three is 181-201°C, zone four is 185-205°C, and zone five is 180-200°C.

[0022] Optionally, the rotation speeds of the first screw extruder and the third screw extruder are both 20 r / min, the rotation speed of the second screw extruder is 40 r / min, and the die head temperature of the three-layer co-extrusion film blowing machine is 230-240°C.

[0023] Optionally, the blowing ratio of the film blowing machine is 2.5.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention uses PLA and PBAT as the main materials of the middle layer, and uses cellulose aerogel and pentaerythritol epoxy oleate as a compatibilizer to improve the interface compatibility of PLA and PBAT, so that the product has good uniformity, excellent mechanical properties and low cost;

[0026] 2. The present invention can effectively remove the gas in the pores of the cellulose aerogel by vacuuming the cellulose aerogel at room temperature, thereby enhancing the structural stability of the cellulose aerogel and avoiding damage to its physical structure by overheating. The pentaerythritol epoxy oleate can fully enter the pores of the cellulose aerogel through ultrasonic stirring, thereby improving the adhesion and interface contact performance of the final middle layer.

[0027] 3. In the present invention, pentaerythritol epoxy oleate is fully introduced into the pores of cellulose aerogel, so that the epoxy groups on the long chain of pentaerythritol epoxy oleate molecules are loaded on the surface of cellulose aerogel, so that the cellulose aerogel can form an anchor point between the molten PLA and PBAT, and the epoxy groups react with the carboxyl groups in the molecules of PLA and PBAT respectively, thereby improving the bonding ability of PLA and PBAT, and ensuring that the middle layer has good longitudinal and transverse mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a comparison chart of the relative biodegradation rates of Examples 1 to 4 in Test Example 2. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1: The present invention provides a biodegradable synthetic resin, the synthetic resin is a three-layer co-extruded film consisting of an outer layer, a middle layer and an inner layer, and the thickness ratio of the outer layer, the middle layer and the inner layer is 1:2:1;

[0031] The outer layer comprises the following components by weight: 50 parts of racemic polylactic acid, 30 parts of ethyl cellulose, 8 parts of silane coupling agent KH-560 and 6 parts of carnauba wax;

[0032] The middle layer includes the following components by mass: 80 parts of PLA, 20 parts of PBAT, 12 parts of cellulose aerogel, 8 parts of pentaerythritol epoxy oleate, 0.5 parts of liquid paraffin and 0.5 parts of stearic acid;

[0033] The inner layer comprises the following components by mass: 65 parts of polyhydroxyalkanoate, 18 parts of L-polylactic acid, 12 parts of ethylene-acrylate-maleic anhydride copolymer, 2 parts of acetyl tributyl citrate, 1 part of TMP6000 and 0.1 parts of tert-butylhydroquinone.

[0034] The preparation method of the synthetic resin comprises the following steps:

[0035] S1. Mixing the outer layer components: firstly put the racemic polylactic acid, ethyl cellulose and carnauba wax into a vacuum oven, vacuum dry them at 45°C for 8h, then transfer them into an internal mixer, add silane coupling agent KH-560 into the internal mixer, set the blending temperature to 180°C, the blending speed to 50r / min, and finally melt-blend for 5min to obtain blend A;

[0036] S2, mixing the middle layer components: first put PLA and PBAT into a vacuum oven, vacuum dry them at 45°C for 8 hours, and then transfer them to an internal mixer, then put the cellulose aerogel into a container and place it in a vacuum chamber, evacuate to 98.7 kPa at room temperature, then gradually add pentaerythritol epoxide oleate, stir ultrasonically for 2 hours, and then transfer to an internal mixer, then add liquid paraffin, acetyl tributyl citrate and stearic acid to the internal mixer, set the blending temperature to 180°C, the blending speed to 50 r / min, and finally melt blend for 5 minutes to obtain blend B;

[0037] S3, mixing the inner layer components: first put the polyhydroxyalkanoate and L-polylactic acid into a vacuum oven, vacuum dry them at 45°C for 8 hours, and then transfer them to an internal mixer, then add ethylene-acrylate-maleic anhydride copolymer, acetyl tributyl citrate, TMP6000 and tert-butylhydroquinone into the internal mixer, set the blending temperature to 180°C, the blending speed to 50r / min, and finally melt blend for 5 minutes to obtain blend C;

[0038] S4, three-layer co-extrusion: firstly, the blend A, the blend B and the blend C are respectively put into the outer material flow channel, the middle material flow channel and the inner material flow channel of the three-layer co-extrusion film blowing machine, and then the blend A, the blend B and the blend C are respectively heated to be melted and extruded from the die head of the three-layer co-extrusion film blowing machine to obtain a mold blank, and finally the mold blank is blown into a film bubble by a blow molding machine;

[0039] S5, cooling and winding: first cool the film bubble to room temperature, then use a film edge trimming machine to trim the film bubble, and finally use a film winding machine to wind the film bubble to obtain synthetic resin.

[0040] Example 2: The present invention provides a biodegradable synthetic resin, the synthetic resin is a three-layer co-extruded film consisting of an outer layer, a middle layer and an inner layer, and the thickness ratio of the outer layer, the middle layer and the inner layer is 1:2:1;

[0041] The outer layer comprises the following components by weight: 60 parts of racemic polylactic acid, 40 parts of ethyl cellulose, 9 parts of silane coupling agent KH-560 and 7 parts of carnauba wax;

[0042] The middle layer includes the following components by mass: 84 parts of PLA, 24 parts of PBAT, 13 parts of cellulose aerogel, 9 parts of pentaerythritol epoxy oleate, 0.7 parts of liquid paraffin and 0.7 parts of stearic acid;

[0043] The inner layer comprises the following components by mass: 70 parts of polyhydroxyalkanoate, 20 parts of L-polylactic acid, 13 parts of ethylene-acrylate-maleic anhydride copolymer, 3 parts of acetyl tributyl citrate, 1 part of TMP6000 and 0.2 parts of tert-butylhydroquinone.

[0044] The preparation method of the synthetic resin comprises the following steps:

[0045] S1. Mixing the outer layer components: firstly put the racemic polylactic acid, ethyl cellulose and carnauba wax into a vacuum oven, vacuum dry them at 48°C for 9 hours, then transfer them into an internal mixer, add silane coupling agent KH-560 into the internal mixer, set the blending temperature to 190°C, the blending speed to 60r / min, and finally melt-blend for 8 minutes to obtain blend A;

[0046] S2, mixing the middle layer components: first put PLA and PBAT into a vacuum oven, vacuum dry them at 48 ° C for 9 hours, and then transfer them to an internal mixer, then put the cellulose aerogel into a container and place it in a vacuum chamber, evacuate to 99.0 kPa at room temperature, and then gradually add pentaerythritol epoxide oleate, ultrasonically stir for 3 hours, and then transfer to an internal mixer, then add liquid paraffin, acetyl tributyl citrate and stearic acid to the internal mixer, set the blending temperature to 190 ° C, the blending speed to 60 r / min, and finally melt blend for 8 minutes to obtain blend B;

[0047] S3, mixing the inner layer components: first put the polyhydroxyalkanoate and L-polylactic acid into a vacuum oven, vacuum dry them at 48°C for 9 hours, and then transfer them to an internal mixer, then add ethylene-acrylate-maleic anhydride copolymer, acetyl tributyl citrate, TMP6000 and tert-butylhydroquinone into the internal mixer, set the blending temperature to 190°C, the blending speed to 60r / min, and finally melt blend for 8 minutes to obtain blend C;

[0048] S4, three-layer co-extrusion: firstly, the blend A, the blend B and the blend C are respectively put into the outer material flow channel, the middle material flow channel and the inner material flow channel of the three-layer co-extrusion film blowing machine, and then the blend A, the blend B and the blend C are respectively heated to be melted and extruded from the die head of the three-layer co-extrusion film blowing machine to obtain a mold blank, and finally the mold blank is blown into a film bubble by a blow molding machine;

[0049] S5, cooling and winding: first cool the film bubble to room temperature, then use a film edge trimming machine to trim the film bubble, and finally use a film winding machine to wind the film bubble to obtain synthetic resin.

[0050] Embodiment 3: The present invention provides a biodegradable synthetic resin, wherein the synthetic resin is a three-layer co-extruded film consisting of an outer layer, a middle layer and an inner layer, wherein the thickness ratio of the outer layer, the middle layer and the inner layer is 1:2:1;

[0051] The outer layer comprises the following components by weight: 70 parts of racemic polylactic acid, 50 parts of ethyl cellulose, 9 parts of silane coupling agent KH-560 and 7 parts of carnauba wax;

[0052] The middle layer includes the following components by mass: 88 parts of PLA, 28 parts of PBAT, 15 parts of cellulose aerogel, 9 parts of pentaerythritol epoxy oleate, 0.8 parts of liquid paraffin and 0.8 parts of stearic acid;

[0053] The inner layer comprises the following components by mass: 75 parts of polyhydroxyalkanoate, 22 parts of L-polylactic acid, 14 parts of ethylene-acrylate-maleic anhydride copolymer, 3 parts of acetyl tributyl citrate, 2 parts of TMP6000 and 0.4 parts of tert-butylhydroquinone.

[0054] The preparation method of the synthetic resin comprises the following steps:

[0055] S1. Mixing the outer layer components: firstly put the racemic polylactic acid, ethyl cellulose and carnauba wax into a vacuum oven, vacuum dry them at 48°C for 9 hours, then transfer them into an internal mixer, add silane coupling agent KH-560 into the internal mixer, set the blending temperature to 195°C, the blending speed to 65r / min, and finally melt-blend for 8 minutes to obtain blend A;

[0056] S2, mixing the middle layer components: first put PLA and PBAT into a vacuum oven, vacuum dry them at 48 ° C for 9 hours, and then transfer them to an internal mixer, then put the cellulose aerogel into a container and place it in a vacuum chamber, evacuate to 95.0 kPa at room temperature, and then gradually add pentaerythritol epoxide oleate, stir ultrasonically for 4 hours, and then transfer to an internal mixer, then add liquid paraffin, acetyl tributyl citrate and stearic acid to the internal mixer, set the blending temperature to 195 ° C, the blending speed to 65 r / min, and finally melt blend for 8 minutes to obtain blend B;

[0057] S3, mixing the inner layer components: first put the polyhydroxyalkanoate and L-polylactic acid into a vacuum oven, vacuum dry them at 48°C for 9 hours, and then transfer them to an internal mixer, then add ethylene-acrylate-maleic anhydride copolymer, acetyl tributyl citrate, TMP6000 and tert-butylhydroquinone into the internal mixer, set the blending temperature to 195°C, the blending speed to 65r / min, and finally melt blend for 8 minutes to obtain blend C;

[0058] S4, three-layer co-extrusion: firstly, the blend A, the blend B and the blend C are respectively put into the outer material flow channel, the middle material flow channel and the inner material flow channel of the three-layer co-extrusion film blowing machine, and then the blend A, the blend B and the blend C are respectively heated to be melted and extruded from the die head of the three-layer co-extrusion film blowing machine to obtain a mold blank, and finally the mold blank is blown into a film bubble by a blow molding machine;

[0059] S5, cooling and winding: first cool the film bubble to room temperature, then use a film edge trimming machine to trim the film bubble, and finally use a film winding machine to wind the film bubble to obtain synthetic resin.

[0060] Example 4: The present invention provides a biodegradable synthetic resin, wherein the synthetic resin is a three-layer co-extruded film consisting of an outer layer, a middle layer and an inner layer, wherein the thickness ratio of the outer layer, the middle layer and the inner layer is 1:2:1;

[0061] The outer layer comprises the following components by weight: 75 parts of racemic polylactic acid, 55 parts of ethyl cellulose, 10 parts of silane coupling agent KH-560 and 8 parts of carnauba wax;

[0062] The middle layer includes the following components by mass: 90 parts of PLA, 32 parts of PBAT, 16 parts of cellulose aerogel, 10 parts of pentaerythritol epoxy oleate, 1 part of liquid paraffin and 1 part of stearic acid;

[0063] The inner layer comprises the following components by mass: 80 parts of polyhydroxyalkanoate, 24 parts of L-polylactic acid, 15 parts of ethylene-acrylate-maleic anhydride copolymer, 4 parts of acetyl tributyl citrate, 2 parts of TMP6000 and 0.5 parts of tert-butylhydroquinone.

[0064] The preparation method of the synthetic resin comprises the following steps:

[0065] S1. Mixing the outer layer components: firstly put the racemic polylactic acid, ethyl cellulose and carnauba wax into a vacuum oven, vacuum dry them at 50°C for 10 hours, then transfer them into an internal mixer, add silane coupling agent KH-560 into the internal mixer, set the blending temperature to 200°C, the blending speed to 70r / min, and finally melt-blend for 10 minutes to obtain blend A;

[0066] S2, mixing the middle layer components: first put PLA and PBAT into a vacuum oven, vacuum dry them at 50°C for 10 hours, and then transfer them to an internal mixer, then put the cellulose aerogel into a container and place it in a vacuum chamber, evacuate to 99.9 kPa at room temperature, then gradually add pentaerythritol epoxide oleate, stir ultrasonically for 5 hours, and then transfer to an internal mixer, then add liquid paraffin, acetyl tributyl citrate and stearic acid to the internal mixer, set the blending temperature to 200°C, the blending speed to 70 r / min, and finally melt blend for 10 minutes to obtain blend B;

[0067] S3, mixing the inner layer components: first put the polyhydroxyalkanoate and L-polylactic acid into a vacuum oven, vacuum dry them at 50°C for 10 hours, and then transfer them to an internal mixer, then add ethylene-acrylate-maleic anhydride copolymer, acetyl tributyl citrate, TMP6000 and tert-butylhydroquinone into the internal mixer, set the blending temperature to 200°C, the blending speed to 70r / min, and finally melt blend for 10 minutes to obtain blend C;

[0068] S4, three-layer co-extrusion: firstly, the blend A, the blend B and the blend C are respectively put into the outer material flow channel, the middle material flow channel and the inner material flow channel of the three-layer co-extrusion film blowing machine, and then the blend A, the blend B and the blend C are respectively heated to be melted and extruded from the die head of the three-layer co-extrusion film blowing machine to obtain a mold blank, and finally the mold blank is blown into a film bubble by a blow molding machine;

[0069] S5, cooling and winding: first cool the film bubble to room temperature, then use a film edge trimming machine to trim the film bubble, and finally use a film winding machine to wind the film bubble to obtain synthetic resin.

[0070] In Examples 1 to 4, the density of racemic polylactic acid is 1.26 g / cm 3 The melt index of racemic polylactic acid is 6.5g / 10min; the density of PLA is 1.24g / cm 3 , the melt index of PLA is 6.1g / 10min, and the density of PBAT is 1.20g / cm 3 , the melt index of PBAT is 42.8g / 10min; PLA is a mixture of racemic polylactic acid and L-polylactic acid, and the mass ratio of racemic polylactic acid to L-polylactic acid is 1:1; the density of polyhydroxyalkanoate is 1.28g / cm 3 The melt index of polyhydroxyalkanoate is 4.0g / 10min, and the density of L-polylactic acid is 1.25g / cm 3 The melt index of L-polylactic acid is 7.0 g / 10 min. The melt indexes of the above materials are measured at a temperature of 190° C. and a load of 2.16 kg.

[0071] In Examples 1 to 4, the outer material flow channel is connected to the first screw extruder, and the temperature parameters of the first screw extruder are set as follows: zone 1 is 154-174°C, zone 2 is 165-185°C, zone 3 is 166-186°C, zone 4 is 166-186°C, and zone 5 is 165-185°C; the middle material flow channel is connected to the second screw extruder, and the temperature parameters of the second screw extruder are set as follows: zone 1 is 166-18 6℃, zone 2 is 117~197℃, zone 3 is 178~198℃, zone 4 is 179~199℃, zone 5 is 178~197℃; the inner layer material flow channel is connected to the third screw extruder, and the temperature parameters of the third screw extruder are set as follows: zone 1 is 169~185℃, zone 2 is 180~200℃, zone 3 is 181~201℃, zone 4 is 185~205℃, and zone 5 is 180~200℃. The speeds of the first and third screw extruders are both 20r / min, the speed of the second screw extruder is 40r / min, the die head temperature of the three-layer co-extrusion film blowing machine is 230~240℃, and the blow-up ratio of the film blowing machine is 2.5.

[0072] Test Example 1

[0073] Test content: The synthetic resins prepared in Examples 1 to 4 were stretched to a thickness of 50 μm as the experimental group, and a film of model C1200 (thickness 50 μm) produced by BASF of Germany was taken as the control group. The tensile properties of the experimental group and the control group were measured with reference to the standard GB / T1040.3-2006, wherein: the stretching rate was 250 mm / min, the strip width was 15 mm, and the results were recorded in Table 1.

[0074] Table 1

[0075]

[0076] As can be seen from Table 1, the synthetic resins prepared in Examples 1 to 4 have good tensile strength, indicating that the use of cellulose aerogel and pentaerythritol epoxy oleate as a compatibilizer can improve the interfacial compatibility of PLA and PBAT, ensuring that the prepared synthetic resin is a tough material.

[0077] Test Example 2

[0078] Test content: The synthetic resins prepared in Examples 1 to 4 were stretched to a thickness of 50 μm, and the degradation performance of the synthetic resins prepared in Examples 1 to 4 was tested under aerobic conditions with reference to the standard GB / T19277.1-2011, wherein the synthetic resins were pre-crushed through a 100-mesh sieve, the culture temperature was 58±2°C, the composting period was no more than 6 months and greater than 45 days, and the relative biodegradation rate was calculated based on the experimental results. If the relative biodegradation rate was greater than 90%, it was considered that the material was completely biodegraded, and the test could be terminated in advance. The experimental results are shown in Table 2 and Figure 1shown.

[0079] Table 2

[0080]

[0081] From Table 2 and Figure 1 It can be seen that the slope of the biodegradation rate of the synthetic resins prepared in Examples 1 to 4 in 0-20 days is smaller than the slope of the biodegradation rate of the synthetic resins prepared in Examples 1 to 4 in 20-40 days, which preliminarily shows that in the process of initial biodegradation, the degradation rate of the synthetic resin increases, and the use of cellulose aerogel and pentaerythritol epoxyoleate as a compatibilizer will not reduce the degradation rate of the synthetic resin in the initial stage. The degradation rate of the sample prepared in Example 4 is better than that of other samples, and it is worthy of promotion and use.

[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A biodegradable synthetic resin, characterized in that: The synthetic resin is a three-layer co-extruded film consisting of an outer layer, a middle layer and an inner layer, and the thickness ratio of the outer layer, the middle layer and the inner layer is 1:2:1; The outer layer comprises the following components by weight: 50 to 75 parts of racemic polylactic acid, 30 to 55 parts of ethyl cellulose, 8 to 10 parts of silane coupling agent KH-560 and 6 to 8 parts of carnauba wax; The middle layer comprises the following components by weight: 40-45 parts of PLA, 20-32 parts of PBAT, 12-16 parts of cellulose aerogel, 8-10 parts of pentaerythritol epoxy oleate, 0.5-1 parts of liquid paraffin and 0.5-1 parts of stearic acid; The inner layer comprises the following components by mass: 65-80 parts of polyhydroxyalkanoate, 18-24 parts of L-polylactic acid, 12-15 parts of ethylene-acrylate-maleic anhydride copolymer, 2-4 parts of acetyl tributyl citrate, 1-2 parts of TMP6000 and 0.1-0.5 parts of tert-butyl hydroquinone; The preparation method of the synthetic resin comprises the following steps: S1. Mixing the outer layer components: firstly put the racemic polylactic acid, ethyl cellulose and carnauba wax into a vacuum oven, vacuum dry them at 45-50°C for 8-10h, then transfer them into an internal mixer, add silane coupling agent KH-560 into the internal mixer, set the blending temperature at 180-200°C, the blending speed at 50-70r / min, and finally melt-blend for 5-10min to obtain blend A; S2, mixing the middle layer components: first put PLA and PBAT into a vacuum oven, vacuum dry them at 45-50°C for 8-10 hours, and then transfer them to an internal mixer, then put the cellulose aerogel into a container and place it in a vacuum chamber, evacuate to 98.7-99.9 kPa at room temperature, then gradually add pentaerythritol epoxy oleate, ultrasonically stir for 2-5 hours, and then transfer to an internal mixer, then add liquid paraffin, acetyl tributyl citrate and stearic acid to the internal mixer, set the blending temperature to 180-200°C, the blending speed to 50-70 r / min, and finally melt blend for 5-10 minutes to obtain blend B; S3, mixing the inner layer components: first put the polyhydroxyalkanoate and L-polylactic acid into a vacuum oven, vacuum dry them at 45-50°C for 8-10 hours, and then transfer them to an internal mixer, then add ethylene-acrylate-maleic anhydride copolymer, acetyl tributyl citrate, TMP6000 and tert-butylhydroquinone into the internal mixer, set the blending temperature to 180-200°C, the blending speed to 50-70r / min, and finally melt-blend for 5-10 minutes to obtain a blend C; S4, three-layer co-extrusion: firstly, the blend A, the blend B and the blend C are respectively put into the outer material flow channel, the middle material flow channel and the inner material flow channel of the three-layer co-extrusion film blowing machine, and then the blend A, the blend B and the blend C are respectively heated to be melted and extruded from the die head of the three-layer co-extrusion film blowing machine to obtain a mold blank, and finally the mold blank is blown into a film bubble by a blow molding machine; S5, cooling and winding: firstly cool the film bubble to room temperature, then use a film edge trimming machine to trim the film bubble, and finally use a film winding machine to wind up the film bubble to obtain the synthetic resin.

2. A biodegradable synthetic resin according to claim 1, characterized in that: The density of the racemic polylactic acid is 1.26 g / cm 3 The melt index of the racemic polylactic acid is 6.5 g / 10 min.

3. The biodegradable synthetic resin according to claim 1, characterized in that: The density of the PLA is 1.24 g / cm 3 The melt index of PLA is 6.1 g / 10 min, and the density of PBAT is 1.20 g / cm 3 , the melt index of the PBAT is 42.8 g / 10 min.

4. A biodegradable synthetic resin according to claim 3, characterized in that: The PLA is a mixture of racemic polylactic acid and L-polylactic acid, and the mass ratio of the racemic polylactic acid to the L-polylactic acid is 1:

1.

5. The biodegradable synthetic resin according to claim 1, characterized in that: The density of the polyhydroxyalkanoate is 1.28 g / cm 3 The melt index of the polyhydroxyalkanoate is 4.0 g / 10 min, and the density of the L-polylactic acid is 1.25 g / cm 3 The melt index of the L-polylactic acid is 7.0 g / 10 min.

6. The biodegradable synthetic resin according to claim 1, characterized in that: The outer material flow channel is connected to the first screw extruder, and the temperature parameters of the first screw extruder are set as follows: zone 1 is 154-174°C, zone 2 is 165-185°C, zone 3 is 166-186°C, zone 4 is 166-186°C, and zone 5 is 165-185°C; The middle-layer material flow channel is connected to the second screw extruder, and the temperature parameters of the second screw extruder are set as follows: zone 1 is 166-186°C, zone 2 is 117-197°C, zone 3 is 178-198°C, zone 4 is 179-199°C, and zone 5 is 178-197°C; The inner material flow channel is connected to the third screw extruder, and the temperature parameters of the third screw extruder are set as follows: zone one is 169-185°C, zone two is 180-200°C, zone three is 181-201°C, zone four is 185-205°C, and zone five is 180-200°C.

7. A biodegradable synthetic resin according to claim 6, characterized in that: The rotation speeds of the first screw extruder and the third screw extruder are both 20 r / min, the rotation speed of the second screw extruder is 40 r / min, and the die head temperature of the three-layer co-extrusion film blowing machine is 230-240°C.

8. The biodegradable synthetic resin according to claim 1, characterized in that: The blow-up ratio of the film blowing machine is 2.5.

Citation Information

Patent Citations

  • A biodegradable PBAT / PLA composite material, its preparation method and applications

    CN111378259B

  • Preparation method of three-layer co-extrusion whole-biodegradable mulching film and the three-layer co-extrusion whole-biodegradable mulching film

    CN106363898A

  • Three-layer co-extrusion full-biodegradable delivery packaging bag and preparation method thereof

    CN109229812A